2016
DOI: 10.1097/md.0000000000002669
|View full text |Cite
|
Sign up to set email alerts
|

Sparing Sphincters and Laparoscopic Resection Improve Survival by Optimizing the Circumferential Resection Margin in Rectal Cancer Patients

Abstract: The goal of rectal cancer treatment is to minimize the local recurrence rate and extend the disease-free survival period and survival. For this aim, obtainment of negative circumferential radial margin (CRM) plays an important role. This study evaluated predictive factors for positive CRM status and its effect on patient survival in mid- and distal rectal tumors.Patients who underwent curative resection for rectal cancer were included. The main factors were demographic data, tumor location, surgical technique,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Nevertheless, it significantly improved survival in patients with a pCR, downstaging, or a negative circumferential margin. 110,111,144,145…”
Section: The Era Of 3d-crtmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, it significantly improved survival in patients with a pCR, downstaging, or a negative circumferential margin. 110,111,144,145…”
Section: The Era Of 3d-crtmentioning
confidence: 99%
“…Nevertheless, it significantly improved survival in patients with a pCR, downstaging, or a negative circumferential margin. 110,111,144,145 Early systematic reviews concluded that preoperative RT at a BED of >30 Gy reduced LR risk and improved OS, 25,146 and that no significant difference was observed in outcomes for different time intervals between conventional neoadjuvant CRT and surgery. 147 Moreover, higher doses increased LR reduction.…”
Section: Early Endpoints: Pathologic Tumor Responsementioning
confidence: 99%
“…Analyses for CRMþ rates based on the definition of 1 mm was performed for the predefined subgroups (Appendix Table 3). The pooled proportion of CRM involvement was significantly lower for restorative procedures (17 which was significantly higher than the pooled 9.0% for the studies in which the majority of the rectal cancer patients were operated upon after 2005 (n ¼ 12 studies; 9,486 patients) 47,53,56,57,66,70,71,75,76,82,88,90 (P ¼ .050).…”
Section: Pooled Proportions Of Crm Involvementmentioning
confidence: 77%